2015
DOI: 10.1016/j.cortex.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the semantic network in Alzheimer's disease: Influence of emotion and concreteness of concepts

Abstract: Semantic deficits are often reported in even the very early stages of Alzheimer's disease (AD), but investigations usually focus on concrete and non-emotional entities, ignoring the broad range of concepts that feature in everyday conversations. Emotional concepts (e.g., snake) have been found to be processed more accurately than neutral ones (e.g., chair) in AD. Our aim here was therefore to explore the dimensions of both concreteness and emotion within the semantic framework, and in particular to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Studies in normal healthy participants have found that emotional valence was accessed earlier than semantic aspects such as concreteness of verbs (Palazova, Sommer, & Schacht, 2013). Furthermore, one study showed that in AD, abstract words deteriorated more quickly than concrete words when there was no emotional valence to the words, but this difference between abstract and concrete words was not observed when emotional words were used (Giffard, Laisney, Desgranges, & Eustache, 2015). This suggests that words may be less prone to deterioration in some neurodegenerative diseases when they are emotionally anchored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in normal healthy participants have found that emotional valence was accessed earlier than semantic aspects such as concreteness of verbs (Palazova, Sommer, & Schacht, 2013). Furthermore, one study showed that in AD, abstract words deteriorated more quickly than concrete words when there was no emotional valence to the words, but this difference between abstract and concrete words was not observed when emotional words were used (Giffard, Laisney, Desgranges, & Eustache, 2015). This suggests that words may be less prone to deterioration in some neurodegenerative diseases when they are emotionally anchored.…”
Section: Introductionmentioning
confidence: 99%
“…This attention bias for positive information is believed to improve memory (the so-called positivity effect), as the more information is attended, the more likely it is to be remembered later on (Carstensen, 2006). Regarding aMCI and AD,research on the impact of emotion and/or valence on memoryhas provided mixed results, reporting either an effect of emotion (Giffard, Laisney, Desgranges, & Eustache, 2015; ), no effect of emotion(Abrisqueta-Gomez, Bueno, Oliveira, & Bertolucci, 2002;Kensinger, Brierley, Medford, Growdon, & Corkin, 2002), an effect of positive valence (Kalenzaga, Piolino, & Clarys, 2014;Maki, Yoshida, Yamaguchi, & Yamaguchi, 2013;Werheid, McDonald, Simmons-Stern, Ally, & Budson, 2011;Werheid et al, 2010) or an effect of negative valence Döhnel et al, 2008;Boller et al, 2002). The question of whether the effect of emotionally-laden material on memory is maintained through self-reference across the spectrum of ADpathology still requires much more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In AD, as well as in other neurodegenerative diseases, this effect has been noted to suffer a reversal. Giffard et al (64) conducted a study in which they compared the processing of different concrete and abstract words that could either have a positive, neutral or negative emotional valence. Their result supports the concreteness effect for neutral concepts, while there is no effect for emotional concepts.…”
Section: The Organization Of the Semantic Networkmentioning
confidence: 99%